Think Aloud Method: Is it effective in Enhancing Indonesian EFL Students’ Reading Comprehension Skills? - Muhammad Tolhah; Sugirin Sugirin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
The aim of this study is to investigate the effectiveness of the think-aloud method in teaching reading comprehension skills. The quasi-experimental research used pre-test and post-test design involving students of tenth grade at state senior high school Bolano in Parigi-Moutong, Sulawesi Tengah, Indonesia in academic 2019-2020 who were selected using probability sampling. The stratified sampling was used to divide the population on some specific characters. Then, a simple random sampling technique was conducted to assign the experimental and control group with 61 total participants. To collect the data, pre-test and post-test were assigned. The tests of reading skills were validated through peer validation and content validity. A split-half method is used to find the reliability of the instruments. The inferential statistics using SPSS 22 were applied to analyze the data, normality test, homogeneity test, and hypothesis testing result. The findings of this study revealed that the think-aloud method had a significant difference in enhancing students’ reading comprehension skills compare to the grammar-translation method. It was indicated by the value of 0.00 in the reading comprehension test which was lower than 0.05. This means that the use of the think-aloud method is effective to enhance students’ reading comprehension skills and help students to be effective readers.